Analisis Manajamen Risiko Pada Pembiayaan Murabahah Di BPRS Al-Washliyah Medan - Wicaksana Dwi Prasetiyo; Nursantri Yanti (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
Sharia people's credit bank (BPRS) is an institution that carries out business activities based on sharia principles and in its activities does not provide services in payment traffic. The level of interest in PT. Many BPRS Al Washliyah choose murabahah financing. This high level of murabahah financing activity can cause high risks faced by the entity providing the financing. Risk management is an effort that must be made to minimize the possibility of loss risks that may occur as a result of problematic murabahah financing transactions. The conclusion from these results is that murabahah financing risk management faced by PT. BPRS AL-Washliyah Medan, namely by persuasive means, if this method cannot be a solution to the existing problems, then PT. BPRS Al-Washliyah Medan resolved this by means of collateral, namely the confiscation/sale of collateral